PENGARUH PEMANFAATAN BEBERAPA JENIS TANAMAN REFUGIA TERHADAP INTENSITAS SERANGAN HAMA PENGGEREK BATANG JAGUNG(Ostrinia furnacalis) PADA PERTANAMAN JAGUNG (Zea mays L.) DI DESA KOTAPULU KABUPATEN SIGI - Fahrul Muhammad; Burhanuddin Nasir (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
Corn is the second most significant food commodity following rice, which is given high priority in boosting food security in Indonesia. The high incidence of pests and diseases in corn plantation can pose a significant threat to food security. The pests attacking corn plants include cob borer, stem borer, and other species. The purpose of this research was to determine the effect of various refugia plants (Zinnia elegans Jaqc, Tagetes erecta L, Cosmos caudatus, and Helianthus annus L) on the severity of corn stem borer (O. furnacalis) attacks on corn (Z. mays L). The research was conducted using a Randomized Block design with five treatments and four replications. The results showed that the use of refugia plants could reduce the intensity of attacks by corn stem borer, although the reduction was not significant. The highest dry weight of corn cobs (7.61 t/ha) was achieved in the Tagetes erecta L treatment.